Green synthesis of silver nanoparticles using Aloe vera extract and assessing their antimicrobial activity against skin infections - Supriya, G.; kumari, S. Chaitanya (International Journal of Scientific Research in Biological Sciences, 2019)
The synthesis of nanomaterials is currently one of the most active in nanoscience branches especially those help to improve the human quality life. Silver ions have the disadvantage of forming complexes and the effect of the ions remained only for short time. This disadvantage have been overcome by the use of silver nanoparticles (AgNPs) which are in inert form and also exhibit antimicrobial function by inducing the production of reactive oxygen species. In fish spas, clients may submerge their hands, feet or whole body in basins with Garra rufa fish, for dead skin removal. Skin infections may result from using these spas. We also focused on identification of some common pathological bacterial and fungal isolates responsible for causing foot cracks. In the present work we have made an attempt to evaluate antibacterial and antifungal activities against various pathogens isolated from fish spa water samples, fish gut and from human foot cracks. The fungal isolates identified were Aspergillus sp., Penicillium sp. and Trichophyton sp., and bacterial isolates as Gram positive and Gram-negative organisms. In this work we report the synthesis of silver nanoparticles by green synthesis reduction method of silver nitrate (AgNO3) solution of different concentrations like 1mM,5mM,10mM using Aloevera plant extract of various dilutions like 4:1,3:2,2:3,1:4 respectively. The results show that higher silver nanoparticles were synthesized by using plant extract and water in the ratio of 3:2 and optimal concentration of silver nitrate was found as 10mM. Green synthesized Silver nanoparticles obtained were characterized by UV−visible spectroscopy and Scanning Electron Microscopy (SEM). The zones of inhibition of synthesized silver nanoparticles against the bacterial and fungal pathogens were variable and comparatively the highest was shown by 3:2 diluted plant extract prepared by using 10mM silver nitrate solution of about 24mm and 20mm against Gram positive and Gram negative organisms respectively isolated from fish spa samples. From the present study, it is concluded that green synthesized silver nanoparticles have wide spectrum antibacterial activity in low concentration than antifungal activity and therefore may be used as an alternative approach in medicine and pharmaceutical field in future.